Climate variables on the hydrographic basin of Uruçuí Preto River – Piauí, Brazil subsidies for the management of water and agricultural resources (Research, Society and Development, 2021)
The knowledge of the climatic characteristics of the hydrographic basins, especially regarding the temporal and spatial distribution of rainfall, the relative humidity of the air and the maximum, minimum and average temperatures of the air, which offer important subsidies to the management of water resources and agriculture. The irregular distribution of rainfall indicates instability in the entry of water into the hydrological system, exercising control over water availability in time and space, the relative humidity of the air influences animal and plant behaviors and the amount of water available in the atmosphere. The temperature, on the other hand, influences the evapotranspiration rates, indicating the energy availability of the environment and, consequently, the environmental water demand. The work presents characteristics of the hydrographic basin of the Uruçuí Preto River (BHRUP), in terms of rainfall, relative humidity, temperature, climatological water balance and climatic regimes. The graphs of annual behavior and seasonal regimes elaborated for 25 pluviometric stations distributed in the interior and around the basin, most of them in operation since the 1960s, followed by the elaboration of average isoietas charts and the one of the rainiest semester, relative humidity of the air, isotherms of the maximum, minimum and average temperatures, and of the letters of potential evapotranspiration, real evaporation and water deficit. The climatic types were appreciated due to the influence of the habitual behavior of the atmosphere on the potential and real environmental demand for water and also on the anthropic demand. The Thornthwaite (1948, 1953) climate system was used, based on the comparison between potential evapotranspiration and rainfall.